PENINGKATAN KINERJA GURU DALAM PEMBELAJARAN MELALUI SUPERVISI KLINIS DI SMP NEGERI 2 KUBU - Basri, Mulyadi (Jurnal Kajian Pembelajaran dan Keilmuan, 2021)
Abstract Teaching feasibility is not sufficient to only measure based on formal education but also to be measured based on how the teacher's performance in learning related to lesson planning and learning implementation.The purpose of this school action research (PTS) is to determine the extent to which principal coaching through clinical supervision can improve teacher performance in learning.In this school action research (PTS) was carried out in 2 cycles, from the results of the actions taken were proven to improve teacher performance in learning, namely by increasing teacher performance in preparing lesson plans from 72.86% in cycle 1, increasing to 99.2% in cycle 2. Then the increase in teacher performance in implementing learning from 71.8% in cycle 1, increased to 98.6% in cycle 2. In other words, clinical supervision carried out by researchers as school principals can improve teacher performance in learning. Keywords: Clinical Supervision, Learning, Teacher Performance